Traditionalism and modernity: issues and perspectives in sociology and social anthropology - Karim, A.H.M Zehadul (Trafford Publishing, 2014)
This book has outlined many aspects of traditionalism and modernity, although the topics here are divergent; the consistent part of it is that all of the authors mostly come from the same disciplines of Sociology and Social Anthropology. The main concern is to find out the socio-cultural More... changes that have occurred due to modernization and development. From that perspective, the book is very useful to understand Sociology and Social Anthropology from diversities based on traditionalism....